Effect of preparation methods on tosufloxacin tosylate/ hydroxypropyl-β-cyclodextrin inclusion complex (Brazilian Journal of Pharmaceutical Sciences, 2023)
The main purpose of this work was to compare the effects of the four preparation methods on the TFLX/HP-β-CD inclusion complex. The effects of different preparation methods on the inclusion complex were investigated by SEM, DSC, PXRD, FT-IR and 1H NMR. All the characterization information indicated that the four preparation methods could cause interaction between TFLX and HP-β-CD, but the inclusion complex prepared by solvent evaporation has more reaction sites. Phase solubility experiments demonstrated that the inclusion reaction was spontaneous. In vitro dissolution experiments showed that the dissolution of the inclusion complex in water was: solvent evaporation method (64.39%) > grinding method (42.37%) > ultrasonic method (40.00%) > freezing method (36.08%), and all higher than pure TFLX and physical mixture. These results suggest that the solvent evaporation is the most suitable method for preparing TFLX/HP-β-CD inclusion complexes.